A Novel Mechanism for Delivering IPTV Traffic in Ethernet Passive Optical Networks - Andrew Tanny Liem (STMIK PONTIANAK, 2016)
Abstract IPTV offers digital television services over Internet Protocol (IP) for the ubscribers at a lower cost. Despite all the attractive IPTV services, it also requires high-speed access networks with the functions of multicasting, Quality-of-Services (QoS) guarantee and so on. In the access networks, Ethernet Passive Optical Network (EPON) is regarded as one of the best technology to meet the higher bandwidth demands applications such as IPTV. There are two common mechanisms used for delivering IPTV to the users in the EPON system such as, dedicated stream and multicast stream. The dedicated stream is not scalable to a large number of clients because of the limited bandwidth and resource consumption at the server side. Conversely, although multicast could be used as a scalable solution for media streaming, but providing such services in the EPON is still challenging due to some limitations in the EPON system. In this paper, we propose a new mechanism that is a Single Copy Broadcast (SCB) with Priority Queue (PQ) mechanism that can accommodate large number of clients IPTV streams without adding extra bandwidth and resources at the Optical Line Terminal (OLT). Simulation results have shown that our proposed mechanism can improve the QoS metrics and system performance in terms of bandwidth consumption and power consumption.Keywords— IPTV, QoS, EPON, Unicast, Multicast, Single Copy Broadcast